How do you solve -3( 5p + 3) - 2( 3- 14p ) = 3( 5+ 4p )?

2 Answers
Mar 10, 2018

p = 30

Explanation:

-3( 5p + 3 ) - 2 ( 3 - 14p ) = 3 ( 5 +4p)

Solving braces on both sides

-15p - 9 - 6 +28p = 15 + 12p

-15p +28p -12p = 15 + 9 + 6

28p - 27p = 30

p = 30

Mar 10, 2018

p=30

Explanation:

-3(5p+3)-2(3-14p)=3(5+4p)

Distribute

(-3)(5p)+(-3)(3)+(-2)(3)+(-2)(-14p)=(3)(5)=(3)(4p)

-15p - 9 - 6 +28p =15+12p

13p - 15= 15 + 12p

Add 15 on both sides

13p - 15 + 15 = 15 + 12p + 15

13p = 12p + 30

Subtract 12p on both sides

13p - 12p = 12p - 12p + 30

p = 30